Total neoadjuvant therapy for rectal cancer: Making sense of the results from the RAPIDO and PRODIGE 23 trials. (May 2021) - Giunta, E.F.; Bregni, G.; Pretta, A.; Deleporte, A.; Liberale, G.; Bali, A.M.; Moretti, L.; Troiani, T.; Ciardiello, F.; Hendlisz, A.; Sclafani, F.
Highlights: TNT is a new standard of care for high-risk stage II and stage III rectal cancers. Selection of the most appropriate TNT schema should be made on case-by-case basis. Better criteria to refine patient selection and minimise under/over-treatment are needed. CRT and SCRT remain options for elderly/unfit patients or stage II low-risk tumours. Abstract: A few months ago, results from two randomised phase III trials of total neoadjuvant therapy (TNT) in locally advanced rectal cancer were presented (RAPIDO and PRODIGE 23), consistently showing better short- and long-term outcomes with TNT as compared with standard neoadjuvant long-course chemoradiotherapy (CRT) or short-course radiotherapy (SCRT). These results represent corroborating evidence in support of a practice that many centres had already implemented based on promising preliminary data. Also, they provide new, high-level evidence to endorse TNT as a new management option in the treatment algorithm of stage II-III rectal cancer in those centres where CRT and SCRT have long remained the only accepted standard neoadjuvant treatments. Having two consistently positive trials is certainly reassuring regarding the potential of TNT as a general treatment approach. Nevertheless, substantial differences between these trials pose important challenges in relation to the generalisability and applicability of their results, and translation of the same into practical clinical recommendations. In this article, we address a number of key questions that the RAPIDO and PRODIGE 23 trials have raised among the broad community of gastrointestinal oncologists, proposing an interpretation of the data that may help the decision making, and highlighting grey areas that warrant further investigation.